2019
DOI: 10.1186/s40902-019-0216-2
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary study for three-dimensional alveolar bone morphologic characteristics for alveolar bone restoration

Abstract: Background The concept of the ideal morphology for the alveolar bone form is an important element to reconstruct or restore the in maximizing esthetic profile and functional alveolar bone restoration. The purpose of this preliminary study is to evaluate the normal alveolar bone structure to provide the standard reference and guide template for use in diagnosing for implant placement, determining the correct amount of bone augmentation in actual clinical practice and producing prostheses based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
1
13
0
4
Order By: Relevance
“…The volume and morphology of new bone formed in an alveolar socket can be assessed by examining 3D images that allow discrimination of the area of the socket from the surrounding normal alveolar bone (7,15). In our study, new bone was observed at dentoalveolar sockets after GBP insertion on micro-CT 3D reconstructed images.…”
Section: Discussionmentioning
confidence: 77%
“…The volume and morphology of new bone formed in an alveolar socket can be assessed by examining 3D images that allow discrimination of the area of the socket from the surrounding normal alveolar bone (7,15). In our study, new bone was observed at dentoalveolar sockets after GBP insertion on micro-CT 3D reconstructed images.…”
Section: Discussionmentioning
confidence: 77%
“…The clinical application of each bone substitute can vary according to defect size, location, and extent. It is also affected by the purpose of the bone graft, the morphology of the recipient bed, and surgeon preference [20]. rhBMP-2 is combined with various forms of scaffolds, including collagen sponges, bone matrix gels, blocks, and particle bones [3,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…As radiografias e tomografias são os métodos mais comuns para a visualização e auxílio no diagnóstico das diferentes condições do tecido ósseo alveolar. Muitos foram os estudos descrevendo as características e a morfologia do osso alveolar em sua forma tridimensional (3D) com as diferentes tomografias computadorizadas (TC) [3,[17][18][19][20].…”
Section: Revisão Da Literaturaunclassified
“…Este conceito também se tornou primordial para o campo da engenharia tecidual, responsável pela criação de tecidos artificiais que ajudam restabelecer ou restaurar o perfil estético e funcional em técnicas de cirurgia de enxerto ósseo. A possibilidade de fabricação de modelos tridimensionais de um osso alveolar personalizado tem acelerado a busca por biomateriais que mimetizem sua morfologia e função de forma ideal [3].…”
Section: Introductionunclassified
See 1 more Smart Citation